Social determinants of health associated with dengue in South America: a systematic review - Mendoza, Gabriela E.; Moreira, Camila J.; Sornoza, Brittany R.; Merchán, Luissana; Andrade, María K. (Revista Gregoriana de Ciencias de la Salud, 2025)
Dengue is a viral disease transmitted by the Aedes aegypti mosquito, common in tropical and subtropical areas of the Americas. This study analyses the social determinants of health (SDH) associated with its incidence in South America, defined by the WHO as the conditions in which people are born, live and work. A systematic review of articles published between 2007 and 2023 identified key factors such as poverty, poor housing conditions, and limited access to drinking water, which favor mosquito reproduction and the spread of the disease. The impact of climate change and the geographical distribution of dengue in the region are also highlighted. The study concludes that addressing this problem requires comprehensive approaches that combine social, environmental, and public policy improvements to mitigate the prevalence and challenges associated with dengue.